Implementation Of Principal Supervision On The Performance Of Teacher In The Learning Process at SMK Negeri 1 Gunungsitoli - Lira Bhineka Jaya Lase; Eka Septianti Laoli; Netti K. Mendrofa (Institute of Computer Science (IOCS), 2022)
The implementation of education in vocational high schools involves many factors, including teachers as teaching staff. The main task of teachers according to Law Number 14 of 2005 is to educate, teach, guide, direct, train, assess, and evaluate students. In carrying out the duties of teachers as educators, work performance is measured periodically through the assessment of teacher performance by the principal as the school leader. This study aims to find out whether there is an impact of the implementation of principal supervision on performance of teacher in the learning process at SMK Negeri 1 Gunungsitoli. The census method was used in this study, with a total of 87 samples drawn from the entire population. Data were collected by questionnaires. Research data collected by using questionnaire method and data analysis used are descriptive statistical analysis and linear regressions. The results of the coefficient of determination test obtained a score of 0.739 which means that the relationship between principal supervision and teacher performance was 73.9% and was categorized closely. The adjusted R Square value was 53.2% where the variance of teacher performance could be explained by the principal supervision variable, while 46.8% of teacher performance was explained by other factors who were not reseached in this study. Based on the results of hypothesis testing, These results show that tcounts (9,827) > t table (1.662) and the significance level of 0.000<0.05. Thus, it can be concluded that there is a positive and significant impact of the implementation of principal supervision on performance of teache in the learning process at SMK Negeri 1 Gunungsitoli.